Синтез та аналіз системи керування за інтегральними показниками якості - Голінко, І. М.; Трегуб, В. Г. (Видавництво Львівської політехніки, 2011)
The nonideal PID control synthesis algorithm using the integral quality index is considered. The transient characteristics is used as plant model, that allows exclud an approximation step.
Keywords: quality index; control system; PID control